Tindak Tutur Representatif dalam Unggahan Media Sosial Instagram @taulebih.id pada tahun 2025 (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Speech acts are one component of pragmatic discussions between speakers and speech partners. Speech acts as a bridge that connects what is said with the speaker's true intention, allowing speech partners to understand the meaning behind the utterance. Understanding context-bound meaning in pragmatics cannot be separated from the concept of speech acts. This research is important because understanding representative speech acts in a sentence can help students improve their ability to explain and convey knowledge clearly and accurately. The results of this study can provide valuable information for Indonesian language teachers in evaluating students' abilities, such as understanding and accurately conveying language materials in accordance with the language's rules and conventions. In addition, it can improve the quality of Indonesian language teaching by providing appropriate and contextual language, thereby facilitating broader development of Indonesian language teaching materials. The method used in this study is qualitative descriptive, which analyzes and describes language units containing representative speech acts in uploads on the Instagram social media @taulebih.id. Data collection in this study was conducted using the listening method, incorporating advanced techniques such as recording and distribution. The analysis identified 168 representative speech acts, comprising 42 statements, 77 pieces of information, 19 suggestions, three complaints, three demands, and 24 reports. In conclusion, each type of representative speech plays a crucial role in conveying information.